An effective approach to fabrication of antifouling ultrafiltration membrane based on zwitterionic polyimide. (November 2017) - Liu, Yang; Ai, Yuping; Huo, Pengfei; Huang, Haitao; Gu, Jiyou
In this study, a new kind of membrane material, an aromatic zwitterionic polyimide (PI) copolymer, was synthesized through a one-pot polymerization reaction by precise variation of the molar ratios of different monomers with specific groups. The zwitterionic PI ultrafiltration (UF) membrane was prepared through an immersion precipitation phase inversion method and thoroughly characterized by scanning electron microscopy, water contact angle measurement, protein adsorption measurement, and UF experiment. The zwitterionic PI membrane showed significantly improved hydrophilicity and permeability and stable antifouling property. The amount of bovine serum albumin adsorbed on the zwitterionic PI membrane was considerably lower compared with the reference PI membrane. According to the cycle UF experiment for protein solution, the zwitterionic PI membrane had a water flux recovery ratio of 86.7%, compared with only 61.1% for the reference PI membrane. Moreover, the irreversible fouling of the zwitterionic PI membrane was significantly decreased, suggesting superior antifouling property. This new approach to the preparation of a zwitterionic polymer seems promising for potential applications in separation membrane.